Pengaruh Kecerdasan Spiritual Dan Gaya Hidup Hedonisme Terhadap Manajemen Keuangan Pribadi Gen Z - putri regina Febrianti; Iman Fauzi Sudirman; Diki Mubarok (Jurnal Akuntansi, Manajemen, Bisnis dan Teknologi, 2025)
This study analyzes the impact of spiritual intelligence and hedonistic lifestyle on personal financial management in generation Z. This research aims to investigate the extent to which these two factors influence the financial management of the younger generation. Quantitative methods were applied in this study by involving 100 generation Z participants in the Tasikmalaya area who were selected through survey techniques. Data collection was carried out digitally using a Google Form questionnaire that utilized a Likert Scale of 1-5 to measure each indicator. Data analysis using SPSS 24 includes three main stages: instrument testing, classical assumption testing, and hypothesis verification. The research findings reveal that spiritual intelligence has a significant positive effect on financial management, while a hedonistic lifestyle tends to have a negative impact on personal financial management. These results are expected to provide valuable contributions in understanding the dynamics of financial management among generation Z, especially related to the role of spiritual aspects and consumptive lifestyles.